The Psychopath Traits as Depicted in Emma Grossman’s Character in The Bad Seed 2018 Film - Ni'mah, Sofia; Valiantien, Nita Maya; Max, Jonathan Irene Sartika Dewi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This research is entitled The Psychopath Traits as Depicted in Emma Grossman’s Character in The Bad Seed 2018 Film. This research purpose is to identify and explain the characterization and psychopath traits portrayed by the main character Emma Grossman in The Bad Seed 2018 Film. The data were analyzed with Psychopath Traits Theory as the main theory by Robert Hare. This research is classified as a qualitative method because the data consist of dialogues and pictures taken from The Bad Seed 2018 Film. The data were generated from film scene, act, and dialogue from film script. The results revealed the characteristics of Emma as the main character who has psychopath traits. The researcher concludes there are twelve psychopath traits of Emma: Superficial charm, a grandiose sense of self-worth, propensity for pathological lying, propensity for manipulation, lack of remorse or guilt, shallow affect, impulsivity, early behavioral problems, poor behavioral control, callousness/lack of empathy, failure to accept responsibility of one’s action, parasitic lifestyle. From the 20 psychopath traits checklist of Robert Hare, Emma has 12 psychopath traits in her character.